2008
DOI: 10.1007/s00125-008-1083-z
|View full text |Cite
|
Sign up to set email alerts
|

Variants of CDKAL1 and IGF2BP2 affect first-phase insulin secretion during hyperglycaemic clamps

Abstract: Aims/hypothesis Genome-wide association studies have recently identified novel type 2 diabetes susceptibility gene regions. We assessed the effects of six of these regions on insulin secretion as determined by a hyperglycaemic clamp. Methods Variants of the HHEX/IDE, CDKAL1, SLC30A8, IGF2BP2 and CDKN2A/CDKN2B genes were genotyped in a cohort of 146 participants with NGT and 126 with IGT from the Netherlands and Germany, who all underwent a hyperglycaemic clamp at 10 mmol/l glucose. Results Variants of CDKAL1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
106
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(117 citation statements)
references
References 11 publications
7
106
2
Order By: Relevance
“…Most notably, all previous studies that used a hyperglycaemic clamp procedure comparable to the one used here confirm the independence of genetic effects on insulin secretion and insulin sensitivity. For instance, the risk variants of CDKAL1, IGF2BP2 [36], TCF7L2 [37] or WFS1 [38] clearly impaired glucose-or GLP-1-induced insulin secretion, but did not impact on insulin sensitivity. It has often been suggested that beta cell dysfunction is uncovered only when insulin resistance creates a strongly increased insulin demand.…”
Section: Discussionmentioning
confidence: 98%
“…Most notably, all previous studies that used a hyperglycaemic clamp procedure comparable to the one used here confirm the independence of genetic effects on insulin secretion and insulin sensitivity. For instance, the risk variants of CDKAL1, IGF2BP2 [36], TCF7L2 [37] or WFS1 [38] clearly impaired glucose-or GLP-1-induced insulin secretion, but did not impact on insulin sensitivity. It has often been suggested that beta cell dysfunction is uncovered only when insulin resistance creates a strongly increased insulin demand.…”
Section: Discussionmentioning
confidence: 98%
“…Patients with the GT+TT genotypes of rs4402960 also showed a better repaglinide therapeutic effect on PINS compared with individuals with the GG genotype. Replication of this research has indicated that IGF2BP2 variants were more likely to be associated with reduced -cell function [80,84]. IGF2BP2 was shown to affect insulin secretion in a previous study.…”
Section: Igf2bp2mentioning
confidence: 73%
“…T2DM patients with different IGF2BP2 genotypes showed various levels of insulin secretion. It has been demonstrated that variants in IGF2BP2 gene affect first-phase insulin secretion and the disposition index detected by hyperglycemic clamps [80]. Interactions between genetic variation in IGF2BP2 and T2DM maybe exerted through this IGF2 pathway and through the insulin pathway.…”
Section: Igf2bp2mentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that variants in cdkal1 influence the risk of T2D from impaired insulin secretion and the Cdkal1 protein may be involved in the regulation of insulin secretion. In contrast, the gene variants are not associated with insulin sensitivity or obesity [9,12]. The association of the variants of cdkal1 with T2D is observed across different ethnic its Cdk5 activity through interaction with p35 and p39 [16].…”
Section: Physiological Functions Of Cdkal1mentioning
confidence: 95%